2011
DOI: 10.1186/1471-2407-11-24
|View full text |Cite
|
Sign up to set email alerts
|

Bim and Mcl-1 exert key roles in regulating JAK2V617Fcell survival

Abstract: BackgroundThe JAK2V617F mutation plays a major role in the pathogenesis of myeloproliferative neoplasms and is found in the vast majority of patients suffering from polycythemia vera and in roughly every second patient suffering from essential thrombocythemia or from primary myelofibrosis. The V617F mutation is thought to provide hematopoietic stem cells and myeloid progenitors with a survival and proliferation advantage. It has previously been shown that activated JAK2 promotes cell survival by upregulating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 57 publications
3
19
0
2
Order By: Relevance
“…In contrast, such effect was not observed in relation to cell lines, characterized by c-KIT mutations or transformed with the Bcr--Abl oncoprotein [6]. Although, up-regulation of the pro-apoptotic protein Bim and down-regulation of the anti-apoptotic Bcl-xL was observed, the exact mechanism of apoptosis related to JAK2 inhibitors remain to be elucidated [7][8][9].…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…In contrast, such effect was not observed in relation to cell lines, characterized by c-KIT mutations or transformed with the Bcr--Abl oncoprotein [6]. Although, up-regulation of the pro-apoptotic protein Bim and down-regulation of the anti-apoptotic Bcl-xL was observed, the exact mechanism of apoptosis related to JAK2 inhibitors remain to be elucidated [7][8][9].…”
mentioning
confidence: 64%
“…Also, Rubert et al [8] suggest that Bim activation plays a key role in regulating the survival of SET-2 cells triggered by JAK2 inhibitor. They found that Bim activation following JAK2 inhibition led to enhanced sequestration of BclxL and Mcl-1 anti-apoptotic proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BCL-2 and BCL-X L expression is increased in PV patients with the JAK2 V617F mutation, and higher JAK2 V617F expression in erythroid precursor cells from PV patients was associated with increased sensitivity to ABT-737 treatment (57). RNA interference-induced knockdown of BIM decreased sensitivity to JAK2 inhibition, implying that JAK2 signaling also represses BIM, whereas MCL-1 knockdown increased apoptosis in JAK2 V617F cells and increased sensitivity to JAK2 inhibition (58). Enforced expression of JAK2 V617F increased MCL-1 expression by STAT3-dependent transcription (59).…”
Section: Jak2 Fusions and The Role Of Bcl-x Lmentioning
confidence: 96%
“…Numerous STAT5 transcriptional targets have been reported in the literature, which, when dysregulated, can promulgate the malignant state in MPN. These include: (1) the PIM kinases PIM-1 and PIM-2, which stimulate cell proliferation and impair apoptosis 18 ; (2) c-MYC and JUNB, which provide an immediate early pro-proliferative response to growth stimuli 19,20 ; (3) CYCLIN D2, p27KIP, and CDC25A, which can disrupt the G 1 /S checkpoint and increase cell cycling 21,22 ; (4) the PU.1 and ID1 transcription factors, which function to increase myeloid differentiation 23,24 ; (5) BCL-XL and MCL-1, which inhibit apoptosis and promote cytokine-independent growth and erythropoietin-independent colony formation 25,26 ; and (6) RAD51, which increases rates of DNA repair and maintains genomic stability to facilitate rapid cell cycling. 27 Consistent with the central role of STAT5 in MPN pathophysiology, Jak2V617F expression is incapable of producing disease in a Stat5a/b-deficient mouse.…”
Section: Aberrant Downstream Consequences Of Jak2v617fmentioning
confidence: 99%